Spotlight on clinical strategies of Chronic Internal Carotid Artery Occlusion: Endovascular interventions and external-intracarotid bypasses compared to conservative treatment - Wu, Junnan; Fang, Chaoyou; Wei, Lingying; Liu, Yibo; Xu, Houshi; Wang, Xiaoyu; Yuan, Ling; Wu, Xiaoya; Xu, Yuanzhi; Zhang, Anke (Frontiers in Surgery, 2022)
Chronic internal carotid artery occlusion (CICAO) has high prevalence and incidence rates, and patients with CICAO can be completely asymptomatic, experience a devastating stroke or die. It is important to note that CICAO causes cerebrovascular accidents. Currently, the extracranial-intracranial (EC-IC) bypass technique is used to treat CICAO. However, many clinical studies showed that EC-IC bypass was not beneficial for many patients with CICAO. Meanwhile, endovascular intervention treatment options for CICAO are evolving, and an increasing number of patients are undergoing endovascular intervention therapy. Accordingly, a review comparing both techniques is warranted. For this review, we searched PubMed and collected relevant case study reports comparing endovascular interventional therapy and internal and external cervical bypass surgeries to provide strategies for clinical treatment.